2021
DOI: 10.3389/fneur.2021.696042
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Neurological Deterioration in Stroke Due to Vertebrobasilar Occlusion

Abstract: Background and Aims: This study explores the predictors of early neurological deterioration (END) in patients with vertebrobasilar occlusion (VBO) in both primary endovascular therapy (EVT) and medical management (MM) groups.Methods: Patients diagnosed with VBO from 2010 to 2018 were included. Comparative and multivariate analyses were used to identify predictors of all-cause END in the EVT group, and END due to ischemia progression (END-IP) in the MM group.Results: In 174 patients with VBO, 43 had END. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
2
5
0
1
Order By: Relevance
“…The incidence of END in PCIS ranged from 5.1-28.57% in previous studies [2,6,14,15], in which the risk of END increased in patients with single small infarcts and vertebrobasilar occlusion [2,14]. Compared with non-END patients, this study found that a higher baseline NIHSS score was associated with the occurrence of END, which was consistent with the results of previous studies[6, 14,15].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The incidence of END in PCIS ranged from 5.1-28.57% in previous studies [2,6,14,15], in which the risk of END increased in patients with single small infarcts and vertebrobasilar occlusion [2,14]. Compared with non-END patients, this study found that a higher baseline NIHSS score was associated with the occurrence of END, which was consistent with the results of previous studies[6, 14,15].…”
Section: Discussionsupporting
confidence: 90%
“…In patients with acute subcortical small infarction (SSI) in the vertebrobasilar artery perforator territory, proximal SSI was signi cantly associated with END, which was explained by focal thrombus, hemodynamic instabilityrelated progressive shedding of unstable plaque covering the vessel, poor collateral circulation, or acute in ammation or secondary edema [14]. Large artery atherosclerosis (LAA) was not associated with END in a study on patients with vertebrobasilar occlusion [2]. However, LAA was found to be associated with END in the acute ischemic stroke population[8], and a multicenter study identi ed intracranial atherosclerosis as a risk factor for PCIS [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, there still remains a gap between minor AVS/AIS group and prodromal vertigo group, as END was infrequent in minor AVS/AIS. Thus, in future studies, risk factors of END in minor AVS/AIS should be identified, such as incomplete occlusions or distal basilar involvements that have predicted END in vertebrobasilar occlusions ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…This issue is important because the END rate in patients with VBAO was over 30% in those with a low NIHSS score in a retrospective study [ 34 ]. However, data regarding predictors of END are limited, and potential factors predictive of END that need to be validated include high blood pressure, shorter onset-to-door times, incomplete occlusions, larger infarct cores, and poorer collaterals [ 35 ].…”
Section: Baseline Neurological Severitymentioning
confidence: 99%